Age Variation of Wood Anatomical Characteristics in Larix cajanderi Tree - Nadezhda I. Blokhina; Olesya V. Bondarenko; Sergey V. Osipov (Wood Research Journal, 2011)
The paper is the first results of the study of age variation of wood anatomy in Larix cajanderi Mayr (Pinaceae). The anatomical study was made from one L. cajanderi tree grown in the optimal habitat for L. cajanderi within areal of this species. Age variability of anatomical characteristics in the direction from pith to bark and along the height of stem is described in detail. Mature wood in L. cajanderi is formed in the base of stem and at breast height in the growth rings numbers 31~40 inclusively, and in the middle of stem in the growth rings numbers 41~50 inclusively. Characteristic features of mature stem wood were not found near the top of tree. Maximal parameters of anatomical characters usually occur in the base of stem. Age variation of wood anatomical characteristics in L. cajanderi tree was obtained for the first time.